2017
DOI: 10.1038/s41598-017-10007-8
|View full text |Cite
|
Sign up to set email alerts
|

The synergy between natural polyphenol-inspired catechol moieties and plant protein-derived bio-adhesive enhances the wet bonding strength

Abstract: Novel soybean meal-based biomimetic (STP) adhesives were fabricated via soybean meal (SM) and enhanced by tannic acid (TA) and polyetheylenimine (PEI) (TAPI) co-crosslinking network based on natural polyphenol-inspired chemistry. The multiple physico-chemical interactions (including intermolecular H-bonding and covalent bonding) between the TAPI co-crosslinking system and SM matrices were examined by the Fourier transform infrared spectroscopy, solid-state 13C nuclear magnetic resonance, X-ray diffraction, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 47 publications
3
42
0
Order By: Relevance
“…In addition, the Michael-addition reaction resulted in the formation of aromatic amine () and carbonyl () groups. Additionally, d' peak at 108 ppm shifted downfield, e' peak at 120 ppm, g' peak at 145 ppm and h' peak at 169 ppm shifted upfield, due to the film formation; these shifts were attributed to the formation of both aromatic imine and amine groups [22].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the Michael-addition reaction resulted in the formation of aromatic amine () and carbonyl () groups. Additionally, d' peak at 108 ppm shifted downfield, e' peak at 120 ppm, g' peak at 145 ppm and h' peak at 169 ppm shifted upfield, due to the film formation; these shifts were attributed to the formation of both aromatic imine and amine groups [22].…”
Section: Resultsmentioning
confidence: 95%
“…1b). The characteristic peaks of TA were observed at 155180, 130155, 105130, and 40100 ppm, corresponding to carbonyl, hydroxyl-substituted phenolic, aromatic and cyclo-aliphatic groups, respectively [22,23]. After the formation of the TA/priamine free-standing film, peaks corresponding to the aliphatic groups of priamine were observed below 60 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating catechol into the polymers imparts these materials with the chemical reactivity of catechol for designing adhesives, antifouling coatings, drug carriers, and antimicrobial polymers [ 26 , 27 , 28 , 29 , 30 ]. Similarly, plant-based polyphenols such as tannic acid (TA) and catechin exhibit intermolecular interactions and crosslinking capability resembling those of catechol [ 31 , 32 , 33 ]. While most scientists utilize these compounds predominantly as a surface anchoring group for promoting interfacial bonding, recent research indicated that catechol generates reactive oxygen species (ROS) as a byproduct during catechol oxidation [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the complex process and the environmental pollution that occurs due to the use of synthetic fibers, natural fibers have received increasingly more attention from domestic scholars due to their advantages of biodegradation and natural regenerability [30,31,32]. Among these natural fibers, silk fiber (SF) is widely used in the textile industry due to its inherently high strength and excellent flexibility [33,34]. Previous research has confirmed that SF has a positive impact on the toughness enhancement modification of various composites, such as poly (butylene succinate), polyurethane, and polyethylene terephthalate [19,35,36,37].…”
Section: Introductionmentioning
confidence: 99%